Design and implementation of traffic light control system based on MQTT protocol - Xu, Bo (2017)
Nowadays, urban traffic congestions have been gaining more and more attention because of the rapidly increasing number of vehicles and limited space for further infrastructure expansion. That’s why the intelligent traffic light control system has played a crucial role in reducing traffic congestions and improving the efficiency of road usage. In order to control real traffic lights after we get a proper traffic lights control strategy, we designed a wireless traffic light system to control the mobile traffic lamps that can be located in any place based on the MQTT protocol. MQTT is a message transport protocol based on publish/subscribe and can be used in many situations, because it is light weighted, open, simple and easy to implement. This thesis aims to implement the real time traffic light control for four traffic lamps at one intersection. The method is general, so the scope of traffic control can be extended easily from a single intersection to a traffic network. In this thesis, we will start from the basic knowledge about the MQTT protocol and the reason why we use MQTT rather than other protocols in this system. And then,we present a site choosing problem and how we set it up. Finally, based on the MQTT protocol, we will introduce how to write programs to control the mobile traffic lamps and how a warning mechanism works. The platform we used in this system is windows, and the programming language is C. After testing its function and performance, this traffic light control system can effectively show the signals of traffic lamps as we expected.